2022
DOI: 10.1149/1945-7111/ac62bf
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Panax Notoginseng Powder in Different Parts Based on the Electronic Nose and Time-Domain Feature Extraction

Abstract: To realize the non-destructive identification of Panax notoginseng powder in different parts, we propose a non-destructive identification method based on the electronic nose and time-domain feature extraction. First, The electronic nose technology combined with statistical analysis method was used to collect and extract nine time-domain characteristics of the response information of Panax notoginseng whole root powder, tap root powder, rhizome powder, and fibrous powder, including the data at 110s, the mean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…To eliminate the redundant information between features, IRIV, VISSA, VISSA‐IRIV were used as the feature selection methods to optimize 825 sound signal feature variables of walnut to improve the generalization ability and recognition accuracy of the model, thus enhancing the model's robustness (Lin et al, 2022).…”
Section: Results and Analysismentioning
confidence: 99%
“…To eliminate the redundant information between features, IRIV, VISSA, VISSA‐IRIV were used as the feature selection methods to optimize 825 sound signal feature variables of walnut to improve the generalization ability and recognition accuracy of the model, thus enhancing the model's robustness (Lin et al, 2022).…”
Section: Results and Analysismentioning
confidence: 99%
“…Principal component analysis (PCA) is a traditional linear feature extraction method and is widely used in data analysis (Uddin et al, 2021). Cevoli et al (2021) tionally, some studies have showed that the modeling performance is influenced by the model the parameters, but there is no fixed selection method for the optimal parameters (Lin et al, 2022;Ying et al, 2017). Equilibrium slime mold algorithm (ESMA) is a novel metaheuristic optimization approach that has not been used for the task of parameter searching.…”
Section: Introductionmentioning
confidence: 99%